Auxiliary Power Units For Greenhouse Operations - R. A. Bucklin; R. W. Henley (EDIS, 2017)
Greenhouses require energy to thrive. Most greenhouses require fans, water pumps, heating equipment for operation. A backup generator will keep a greenhouse operational with uninterruptible power supply. When selecting a generator, it is crucial to know how much power the backup generator needs to maintain the essential operations of the greenhouse. Besides, choosing a proper unit and installing and operating it correctly are critical for success. This article provides guidelines for generator selection and operation.